Analisis Pengelolaan dan Pengembangan Usaha Mikro Kecil dan Menengah - Roni Lawaldy; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
The purpose of this study is to describe business management, analyze the internal and external environment, and plan business development at the Rengginang Nurhayati Chips Business. The data collection method used in this study was interviews. The data analysis method used is descriptive qualitative analysis. Based on the results of data analysis, the authors found that the internal environmental management of Rengginang Nurhayati's Chips Business has been running well in terms of human resources, financial aspects, and production and operational aspects. Meanwhile, the external environmental analysis shows that Rengginang Nurhayati Chips has a weak competitive position because it does not have product differentiation. The strategy used by the company is a market development strategy obtained from the results of the SWOT analysis and the grand strategy matrix.